1937
DOI: 10.1021/ja01286a055
|View full text |Cite
|
Sign up to set email alerts
|

The Composition of Grignard Reagents as Determined by Precipitation with Dioxane

Abstract: The salt was dehydrated completely at 78°over phosphorus pentoxide. A sample of the salt weighing 25.270 ing. dried at room temperature over phosphorus pentoxide when completely dehydrated at 78°lost 0.378 mg. weight, or 1.50%. This dehydrated salt was analyzed for nitrogen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

1942
1942
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…Conducting the iron-catalyzed hydromagnesiation of styrene in d 8 -tetrahydrofuran gave a mixture of (1-phenylethyl)magnesium bromide ( 2 ; RMgBr) and bis(1-phenylethyl)magnesium ( 3 ; R 2 Mg), which could be observed at room temperature (25 °C) in a ratio of 1:1.5, corresponding to an equilibrium constant ( K eq ) of 0.44 (Scheme ). , Characterization was aided by perturbation of the Schlenk equilibrium to favor either organomagnesium species. Addition of 1,4-dioxane resulted in the precipitation of MgBr 2 ·(dioxane) to give a majority of 3 , while addition of MgBr 2 led to an increase in 2 (Figure ). Two-dimensional NMR spectroscopy was used to identify and fully characterize 2 and 3 .…”
Section: Resultsmentioning
confidence: 99%
“…Conducting the iron-catalyzed hydromagnesiation of styrene in d 8 -tetrahydrofuran gave a mixture of (1-phenylethyl)magnesium bromide ( 2 ; RMgBr) and bis(1-phenylethyl)magnesium ( 3 ; R 2 Mg), which could be observed at room temperature (25 °C) in a ratio of 1:1.5, corresponding to an equilibrium constant ( K eq ) of 0.44 (Scheme ). , Characterization was aided by perturbation of the Schlenk equilibrium to favor either organomagnesium species. Addition of 1,4-dioxane resulted in the precipitation of MgBr 2 ·(dioxane) to give a majority of 3 , while addition of MgBr 2 led to an increase in 2 (Figure ). Two-dimensional NMR spectroscopy was used to identify and fully characterize 2 and 3 .…”
Section: Resultsmentioning
confidence: 99%
“…The effect of different R groups and of the halide substituents on the Schlenk equilibrium was further investigated by Schlenk, Jr. and other groups. , It was found that the addition of dioxane to solutions of Grignard reagents not only led to precipitation of MgX 2 and RMgX as their dioxane adducts but also could shift the equilibrium to the right. , This offered a simple and general approach to the preparation of halide-free diorganomagnesium compounds. Furthermore, the solvent and temperature dependence of the Schlenk equilibrium in the presence of dioxane was studied .…”
Section: Introductionmentioning
confidence: 99%
“…Dialkylmagnesium is often obtained by displacement of the Schlenk equilibrium of the corresponding alkylmagnesium bromide in ethereal solution. In a first step, 1-(3-bromopropyl)-2,2,5,5-tetramethyl-1-aza-2,5-disilacylopentane ( 1 ) (Scheme ) was isolated by reacting 1,1,4,4-tetramethyl-1,4-dichloro-1,4-disilabutane with 3-bromopropylamine hydrobromide (see Supporting Information Figure S1). Di­(1-(propyl)-2,2,5,5-tetramethyl-1-aza-2,5-disilacylo­pentane)­magnesium ( 3 ) was further successfully obtained by addition of 1.5 equiv of dioxane to a THF solution of 1-(propyl)-2,2,5,5-tetramethyl-1-aza-2,5-disilacylopentane magnesium bromide ( 2 ) obtained from 1 .…”
Section: Resultsmentioning
confidence: 99%